A Most Inhospitable Coast: The Report of Lieutenant William Hobson’s 1859 Search for the Franklin Expedition on King William Island - Stenton, Douglas R. (ARCTIC, 2014)
Lieutenant William R. Hobson’s 1859 search for traces of the Franklin expedition on the west coast of King William Island resulted in several major discoveries that include an official record containing the dates of Sir John Franklin’s death, of the abandonment of HMS Erebus and HMS Terror, and of the departure of the ship’s company for the Back River. Information derived from Hobson’s report appeared in McClintock’s published account of the expedition, and it has been referenced in other works, but the report itself was never published. Recent investigations of Franklin archaeological sites on the Victoria Strait coast of King William Island by the Government of Nunavut, including sites first discovered by Hobson, served as a catalyst for locating Hobson’s full descriptions of his findings. The report includes general observations on weather, ice conditions, and wildlife encountered, and his detailed descriptions of several Franklin expedition sites are potentially valuable sources of information for ongoing archaeological investigations. La recherche de traces de l’expédition de Franklin réalisée sur la côte ouest de l’île King William par le lieutenant William R. Hobson en 1859 a donné lieu à plusieurs découvertes d’envergure, dont un document officiel renfermant les dates du décès de Sir John Franklin, de l’abandon du HMS Erebus et du HMS Terror ainsi que du départ de l’équipage du navire pour la rivière Back. Des renseignements dérivés du rapport de William Hobson figurent dans le compte rendu publié par McClintock au sujet de l’expédition. Ces renseignements ont également été repris dans d’autres ouvrages, mais le rapport en soi n’a jamais été publié. Des enquêtes récentes effectuées par le gouvernement du Nunavut aux sites archéologiques de Franklin sur la côte du détroit de Victoria, à l’île King William, visant notamment des sites qui avaient d’abord été découverts par William Hobson, ont servi de catalyseur à la découverte des descriptions complètes des observations de William Hobson. Le rapport ...